Dinamika Perubahan Kurikulum: Kebijakan Perubahan Kurikulum 2013 PAUD - Istiqomah, Laelatul (Program Studi Pendidikan Guru Raudlatul Athfal, UIN Sunan Kalijaga Yogyakarta, 2016)
One of the educational problems in Indonesia is the curriculum. Along with the development and challenges of the times, the curriculum is always run into changing, as well the systemic and purposefull development. the curriculum implementation should be able to realize the vision, mission, and goals of national education gradually. the most basic of change and development of curriculum  is changing and developing early childhood curriculum. because the quality of Early Childhood Education determines the quality of Indonesian human resources (HR) in the future, one of which is the 2013 early childhood curriculum. currently early childhood education has had its own curriculum, because during this time early childhood education doesn't have an curriculum. the 2013 Early Childhood curriculum  is expected to encourage the development of learners optimally.